The study of impediments to successful exploitation of some industrial units in Ardabil industrial town (Global Journal of Management and Business Research, 2012)
Industrial towns play an eminent role in industrial expansion of the region and the country (Iran). Moreover, these units increase the rates of employment. Industrial authorities and custodians have established many basic systems and services in these towns. Despite the existence of infrastructural facilities (such as water, electricity, gas, green field sites etc.) in Ardabil industrial towns, most of industrial units have stopped their activities or their activities are not continuous. The aim of this research is to study the reasons for failures of some industrial units in industrial towns of Ardabil province and to suggest some surveying procedures for decreasing these failures. The hypotheses of this research include difficulties affecting some of industrial units in industrial towns of Ardabil province which taken from research literature. The selected tool for testing research hypothesis was questionnaire, which included 30 questions related to designed hypotheses. These questionnaires were distributed among statistical population (production and business administrators of the industrial units, which stopped their activities). We used one-sampled T-test for testing of hypotheses, and Friedman#x2019;s test for classifying of hypotheses. The results of hypotheses testing showed that some factors likeoutlet problems, difficulty in reimbursing of received facilities concerning primary investment, working capitals, and technological problems are effective in inactivity of Ardabil industrial units.
Keywords: industrial unit; industrial town; exploitation; Ardabil